Proses Komunikasi Empatik Antara Perawat Dengan Pasien Lansia di Panti Jompo Tresna Werdha, Kasihan, Bantul - Putri, Devi Lianda; Suciati (Universitas Muhammadiyah Yogyakarta, 2023)
Empathic communication is a way to gain awareness and understanding of the conditions of other people or elderly patients through communication. Thus, the empathic communication process plays an important role in establishing a closeness between nurses and elderly patients. Empathic communication can be manifested in the form of attention, care, and being able to feel what the elderly are experiencing. The purpose of this study is to describe in detail the process of Empathic Communication Between Nurses and Elderly Patients at the Tresna Werdha Nursing Home, Kasihan, Bantul. The approach used by researchers is qualitative with descriptive type. The data collection technique used was in-depth interviews (in-depth interviews) and observation of nurse informants and the elderly. Retrieval of informants using sampling techniques purposive namely by setting the criteria of informants based on research needs. Nurse informants include those who have worked for at least 10 years, while elderly informants are over 60 years old and have been at the Tresna Werdha Bantul Nursing Home for at least 1 year. Based on the results of the study, shows that empathic communication has been carried out by nurses, namely by giving attention and care. The form of attention that nurses pay to elderly patients is by reminding them to take medicine, feed them, wash them, remind them to pray and understand sign language for the elderly. The forms of caring for nurses include being patient, respecting every word the elderly say, respecting and giving physical touch to elderly patients. However, in the process of empathic communication between nurses and elderly patients, there are several obstacles experienced by nurses, including unstable elderly emotions, misperceptions, and having to speak repeatedly. Efforts to overcome these obstacles are to create a calm atmosphere and serve wholeheartedly for the different conditions of the elderly.